Persepsi Dan Penghargaan Masyarakat Atas Doktrin Pemisahan Ruang Publik Dan Domestik Berbasis Gender Di Yogyakarta - Astuti, Dwi (MAJAPAHIT POLICY, 2022)
The division of roles in society has historically remained faithful to gender, namely male and female.Although the basis of this division still stands, it always causes debate from time to time. DebateThese appear related to the expressions "worthy" and "appropriate". What jobs are appropriate and appropriate for men andappropriate and appropriate for women. Along with the development of society, especially from an agrarian society towardsindustrial society, the appropriate and appropriate measure is constantly changing. Demands for family needs, job opportunities for womenand the high skills and knowledge of women are the reasons why women's roles shift from the domestic sphereinto the public domain. However, because domestic work is considered to have no economic value, women who have beendoing domestic work is less valued than men doing work for a living. StudyThis study aims to see if the shift of women working in the public sphere also has an impact on the same awardagainst men. The research was conducted with qualitative methods. From the first research, it was found that the condition of the community was no longerin accordance with the initial division of roles, that is, men work in the public sphere and women in the domestic sphere. Second,It is true that earning a living is more valued than domestic work. Second, nurture theory is more provennamely the division of roles is not natural but the foam is changed. Third, society really appreciates the role of making a livingcompared to domestic roles.